Liberal Feminism Value in Britney Spears’s Selected Songs: Stronger and My Prerogative - Eriani Indah Lestari; Nurochman Nurochman (ITScience (Information Technology and Science), 2022)
Literary work is part of human thought expressed in written form or spoken. A heartfelt Literary work is one that is honest, true to experience and human nature, and therefore can tell the truth about the human experience. All written materials are included in the definition of literature. It includes a wide range of general categories such as novels, dramas, and poems, and the song is also included in poem form. Many approaches can be used to analyze a literary work, one of which is a feminist approach. Feminism can be used to critique literary works. Literature can be analyzed from the perspective of women using a feminist approach. There are many types of feminism that have been present in today's era, one of which is liberal feminism. Liberal feminism is freedom as personal autonomy and political autonomy. The purpose of this study is to analyze the liberal feminism values contained in the chosen song of the singer Britney Spears by using the theory of Baehr and Amy (2021). The method used in this research is a qualitative method. The results of this study indicate that the values of liberal feminism found are being free of the limits set by patriarchal paternalistic and moralistic laws (3 data), and having access to options (2 data). Also, in this research, the researcher found the most dominant liberal feminism value in Britney Spears’s selected songs is which has to be free of the limits set by patriarchal paternalistic and moralistic laws 3 data.